2022
DOI: 10.3389/fitd.2022.847109
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Immune Responses and Infection Resistance in Aedes aegypti and Other Hematophagous Insect Vectors

Abstract: Sexual dimorphism in immune function is prevalent across different species, where males trade their ability to fight pathogens for a practical reproductive function while females favor an extended lifespan. In insects, these differences in immune function reflect an evolutionary life strategy, where females have a presumably more robust immune system than insect males. Here, we evaluate immune functioning in four male and female insect vectors, Aedes aegypti (Diptera, Culicidae), Anopheles aquasalis (Diptera, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…gambiae, although the maximal densities in the two species were similar. We also found sexual dimorphism in infection dynamics, with males harbouring on average more spores than females, as is generally observed [51][52][53][54][55][56][57] .…”
Section: Discussionsupporting
confidence: 82%
“…gambiae, although the maximal densities in the two species were similar. We also found sexual dimorphism in infection dynamics, with males harbouring on average more spores than females, as is generally observed [51][52][53][54][55][56][57] .…”
Section: Discussionsupporting
confidence: 82%
“…Female infection appears to have little or no effect on female behavior or likelihood of mating. This is surprising, however, as a recent study of several insects demonstrated that males and females utilize different strategies in response to infection; while males consistently show a stronger response, females show tolerance (Barletta Ferreira et al., 2022). Females may be tolerant of infection in order to conserve energetic resources for their progeny.…”
Section: Discussionmentioning
confidence: 97%
“…The extent of networking occurring with other species in complex ecological communities will also affect host finding, biting and disease transmission [ 36 ]. Other determinants include the sex and developmental stage of the vector [ 60 , 61 ], as well as physiological factors such as the host nutrition [ 62 ] and the fitness costs of immunity [ 63 ]. In addition, the route of entry and survival in the host will also dictate the nature of the immune response [ 64 ].…”
Section: Insect Vectors Of Diseasementioning
confidence: 99%